Effect of feeding Leucaena leaf-meal on certain biochemical parameters of liver in layers* - Bhatnagar, R; Kataria, M (The Indian Journal of Animal Sciences, 2012)
In the liver of White Leghorn hens, the biochemical changes due to incorporation of Leucaena leucocephala (subabul) leaves in commercial poultry diet were studied. Lactate dehydrogenase, lipid peroxidation, glutathione-S-transferase and glutathione reductase activity altered in response to Leucaena leucocephala leaf-meal feeding. The results indicate that high level of LLM incorporation in diet may lead to oxidative stress, tissue damage and leakage of hepatic enzymes because of presence of toxic components in subabul.